Flavonoid Extraction From Papaya (Carica Papaya L.) Seed Using Ultrasound – Assisted Extraction Method and Determination of Its SPF Value - Budi Nursanto, Eduardus; Wijaya, Rachel; Permata Sari, Alifiana (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2023)
Synthetic compounds with photoprotective property have their limited concentration in sunscreen formulation. Therefore, reaching the maximum UV protection by themselves is difficult. Natural compounds are good consideration to include in sunscreen formulations. Papaya seeds contain large amounts of nutraceutical compounds. However, their presence is often considered as waste. One of many benefits it has is due to the presence of flavonoids, phenols, alkaloids, saponins, and tannins. Flavonoid is one of the alternative compounds that provide beneficial effects on skin UV-protection. Therefore, this study aimed to extract the flavonoid compounds in papaya seeds and test its sun protection factor (SPF) value. Extraction was carried out by varying the mass ratio of the solid/solvent (1:10, 1:20, and 1:30), and the solvent concentration of ethanol (50%, 70%, and 96%) at 45oC for 45 minutes. The results of this study indicate the presence of these compounds in papaya seed extract which was extracted using the ultrasound-assisted extraction method with the maximum extraction yield (11.888%) obtained at 1:30 mass ratio with a 50% ethanol concentration; the highest total flavonoid content was 2.854 mg quercetin equivalent (QE)/g papaya seed at 1:30 ratio with 96% ethanol concentration, and the highest SPF value was at a 50% ethanol concentration which was 12.0775 (at 300 ppm).